Dehydrogenative coupling promoted by copper catalysts: a way to optimise and upgrade bio-alcohols. Issue 6 (6th March 2017) - Scotti, Nicola; Zaccheria, Federica; Evangelisti, Claudio; Psaro, Rinaldo; Ravasio, Nicoletta
Abstract : A one-pot one-step transformation of butanol into butyl butanoate takes place with excellent yield on a Cu/ZrO2 catalyst. Abstract : A process for the one-step transformation of butanol into butyl butyrate has been set up by using a copper/zirconia catalyst. Yields of up to 98% can be obtained at 250 °C by withdrawing the H2 formed. The high activity has been investigated through STEM analysis of the catalyst and FT IR spectroscopy of the substrate adsorbed on the catalyst surface.